PENGARUH LAMA PERENDAMAN HORMON TIROKSIN TERHADAP DAYA TETAS TELUR, PERTUMBUHAN, DAN KELANGSUNGAN HIDUP LARVA IKAN MAS KOKI (Carassius auratus) - Manurung, Septina; Basuki, Fajar; Desrina, - - (Journal of Aquaculture Management and Technology, 2017)
Ikan Mas Koki (Carassius auratus) merupakan salah satu jenis ikan hias yang sangat digemari masyarakat serta memiliki nilai ekonomis yang sangat tinggi. Namun derajat penetasan dan pertumbuhan ikan mas koki sangat rendah. Salah satu upaya yang dapat dilakukan untuk mempercepat daya tetas, pertumbuhan dan kelangsungan hidup larva ikan mas koki yaitu melalui ransangan hormonal seperti hormon tiroksin. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian hormone tiroksin terhadap HR, SR larva ikan mas koki (C. auratus) dan untuk mengetahui pengaruh lama waktu perendaman hormon tiroksin yang terbaik untuk meningkatkan daya tetas, pertumbuhan serta kelangsungan hidup larva ikan mas koki (C. auratus). Penelitian ini menggunakan metode eksperimental dengan 4 perlakuan dan 3 kali ulangan. Perlakuan dalam penelitian ini yaitu Perlakuan A (control), B (perendaman hormon tiroksin 8 jam dengan dosis 0,10 mg/l), C (perendaman hormon tiroksin 16 jam dengan dosis 0,10 mg/l), dan D (perendaman hormon tiroksin 24 jam dengan dosis 0,10 mg/l). Data yang diamati meliputi daya tetas telur (HR), survival rate (SR), laju pertumbuhan spesifik, dan kualitas air. Hasil penelitian menunujukkan bahwa daya tetas telur ikan mas koki pasca perendaman hormon tiroksin berpengaruh nyata (P≤0,01) dengan hasil terbaik terdapat pada perlakuan D 77.67%±1.15, sedangkan tingkat kelulushidupan serta laju pertumbuhan spesifik juga menunjukkan tidak berpengaruh nyata (P≥0,01). Sedangkan kualitas air selama pemeliharaan masih dalam kisaran layak untuk budidaya ikan mas koki. Goldfish (C. auratus) is one type of ornamental fish that is very popular community and has a very high economic value. But the degree of hatching and growth of the goldfish is very low. One effort that can be done to accelerate the hatchability, growth and survival of goldfish larvae is through hormonal stimulation such as thyroxine hormone. This study aims to determine the effect of thyroxine hormone on HR, SR chef larvae (C. auratus) and to determine the effect of longest time of thyroxine hormone immersion to increase hatchability, growth and survival of goldfish larvae (C. auratus). This research used experimental method with 4 treatments and 3 replications. The treatments in this study were Treatment A (control), B (8 hours of thyroid hormone immersion with a dose of 0.10 mg / l), C (16 hours of thyroxine hormone with a dose of 0.10 mg / l), and D (hormone immersion 24 hours of thyroxine at a dose of 0.10 mg / l). Observed data included egg hatchability (HR), survival rate (SR), specific growth rate, and water quality. The results showed that the hatchability of goldfish eggs after soaking the hormone thyroxine significantly (P≤0,01) with the best results was found in treatment D 77.67% ± 1.15, whereas the survival rate and the specific growth rate also showed no significant effect (P≥ 0.01). While the quality of water during maintenance is still within a reasonable range for the cultivation of the goldfish. Goldfish (C. auratus) is one type of ornamental fish that is very popular community and has a very high economic value. But the degree of hatching and growth of the goldfish is very low. One effort that can be done to accelerate the hatchability, growth and survival of goldfish larvae is through hormonal stimulation such as thyroxine hormone. This study aims to determine the effect of thyroxine hormone on HR, SR chef larvae (C. auratus) and to determine the effect of longest time of thyroxine hormone immersion to increase hatchability, growth and survival of goldfish larvae (C. auratus). This research used experimental method with 4 treatments and 3 replications. The treatments in this study were Treatment A (control), B (8 hours of thyroid hormone immersion with a dose of 0.10 mg / l), C (16 hours of thyroxine hormone with a dose of 0.10 mg / l), and D (hormone immersion 24 hours of thyroxine at a dose of 0.10 mg / l). Observed data included egg hatchability (HR), survival rate (SR), specific growth rate, and water quality. The results showed that the hatchability of goldfish eggs after soaking the hormone thyroxine significantly (P≤0,01) with the best results was found in treatment D 77.67% ± 1.15, whereas the survival rate and the specific growth rate also showed no significant effect (P≥ 0.01). While the quality of water during maintenance is still within a reasonable range for the cultivation of the goldfish.